RESPONSE OF MAIZE TO FOLIAR APPLICATION OF ZINC AND AZOTOBACTER INOCULATION - esmaeili, mohammadali; Heidarzade, Ayoub; Gholipour, Mounes (Journal of Agricultural Sciences (Belgrade), 2016)
In order to investigate the effects of zinc and Azotobacter on maize production properties under different regime of urea as chemical fertilizer an experiment was conducted at research field of Sari Agricultural Sciences and Natural Resources University during the cropping season of 2014. The Nitrogen chemical fertilizer was used as the main plot (100, 200 and 300 kg urea/ha), Azotobacter (inoculation and non-inoculation) and Zinc (0, 500, 1000 ppm as foliar application) were considered as the second and third agents in factorial arrangement, respectively. Grain yield, biological yield and total protein content of each treatment were assessed. The results indicated that, foliar application of Zn had significantly effect on all studied traits. The highest Grain yield was related to Zn1 in each urea application and also between biological fertilizer treatments the highest yield was observed by inoculation treatment. Between all studied treatment the maximum Grain yield (with 10.23 ton/ha) was related to non-inoculation treatment in Zn1 for urea 300 kg/ha. The various significantly differences were observed in urea 200kg/ha treatment for biological yield. So that, highest biological yield was related to zn1+ inoculation treatment. There are no significantly differences between Azotobacter inoculation and non-inoculation for each level of zinc applications among of urea 300 kg/ha treatment. Finally, it might concluded that, by combining some management strategies in maize production using of chemical fertilizer (the main causes of environmental and groundwater resources pollution) could be reduced.